2020
DOI: 10.3390/ani10030481
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Encapsulated Essential Oils Improve Production Performance of Coccidiosis-Vaccine-Challenged Broiler Chickens

Abstract: The present study was conducted to evaluate the encapsulated essential oils (EEO) as an alternative to anticoccidials using a coccidiosis vaccine challenged model in broiler chickens. A total of 600 one-day-old male broiler chicks were provided with no added corn/soybean-meal-based control diet or diets that contained either salinomycin (SAL) or thymol- and carvacrol-based EEO at 60 and 120 mg per kg of diet. Before challenge at 21 days, each treatment had 10 replicates except for the no-added control group, w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 40 publications
0
28
0
Order By: Relevance
“…At d 14, half of the control group (challenged control; INFECT) and all of the treated groups were challenged with 25× the recommended dose (5 × 10 4 oocysts per bird) of the live coccidiosis vaccine (Coccivac®-D, Intervet/Merck Animal Health, Omaha, NE, USA). We selected the 25× manufacturer’s recommended dose of the live coccidiosis vaccine in an attempt to induce mild to moderate coccidiosis without mortality [ 18 ]. In addition, the authors chose the challenge time point at d 14 posthatch so that the anticoccidial effect of the tested additives could be determined on d 20 onward by measuring various parameters such as Eimeria -specific gut lesions, oocyst output, and growth performance.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…At d 14, half of the control group (challenged control; INFECT) and all of the treated groups were challenged with 25× the recommended dose (5 × 10 4 oocysts per bird) of the live coccidiosis vaccine (Coccivac®-D, Intervet/Merck Animal Health, Omaha, NE, USA). We selected the 25× manufacturer’s recommended dose of the live coccidiosis vaccine in an attempt to induce mild to moderate coccidiosis without mortality [ 18 ]. In addition, the authors chose the challenge time point at d 14 posthatch so that the anticoccidial effect of the tested additives could be determined on d 20 onward by measuring various parameters such as Eimeria -specific gut lesions, oocyst output, and growth performance.…”
Section: Methodsmentioning
confidence: 99%
“…On 6 d post coccidiosis vaccine challenge (d 20 posthatch), the lesion score was measured on the duodenum of the small intestine [ 18 ]. However, it should be noted that coccidiosis vaccine used in this study contained multiple Eimeria species that can affect various segments of intestine ranging from duodenum to ceca.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al [39] further confirmed that the administration of capsicum and curcumin longa oleoresins affected the microbial population by increasing abundance of Lactobacillus and operational taxonomic units, while reducing the population of Selenihalanaerobacter in two chicken breeds (Ross and Cobb). Cinnamaldehyde and Oleoresins (Capsicum and Turmeric) have been reported to regulate host immunity against E. tenella through elevation of T helper cells and cytokines (FN-c and IL-6) and body weight gain in poultry [42]. A combination of curcuma and capsicum exert synergistic effects against coccidiosis by enhancing innate immunity.…”
Section: Stimulation and Stabilisation Of Gut Microbiota Through Phytobioticsmentioning
confidence: 99%
“…Avian coccidiosis is caused by several distinct of Eimeria species including, E. acervulina, E. maxima, and E. tenella, affecting different sites from the duodenum to ceca (4). Eimeria infections cause decreased nutrient absorption and egg production as well as a retarded growth rate, a suppression of humoral and cell-mediated immune responses, and a high mortality resulting thus in enormous economic losses (US $3 billion) to the poultry industry worldwide (4). Used litters or chick delivery boxes could be primary sources of Eimeria species.…”
Section: Introductionmentioning
confidence: 99%